P127 Developing a colorectal cancer risk prediction tool for patients with ulcerative colitis and low-grade dysplasia. (16th January 2018) - Kabir, M; Curtius, K; Al-Bakir, I; Choi, C -H R; Graham, T; Wilson, A; Hart, A
Abstract: Background: The natural history and prognosis of low-grade dysplasia (LGD) in ulcerative colitis (UC) is uncertain which makes communication to patients of their colorectal cancer (CRC) risk and management options (colectomy vs. enhanced colonoscopic surveillance) very challenging. An extensive analysis of the significant risk factors and outcomes of 172 UC patients with histologically diagnosed LGD between January 1993 and December 2012 from the IBD surveillance database at St Mark's Hospital has been reported by our team. 1 Using these data our objective was to develop a novel patient-friendly online CRC risk prediction tool, Ulcerative Colitis Cancer Risk Estimator (UC-CaRE), which can be used to aid in shared decision-making when LGD is diagnosed in UC. Methods: The model requires user input of the seven variables found to be significantly associated with HGD/CRC development ( p < 0.002) in the univariate Cox proportional hazards model analyses in the St Mark's dataset 1 : macroscopic shape of the LGD lesion, largest lesion size, presence of stricture, metachronous lesions found during follow-up, a previous diagnosis of "indefinite for dysplasia", multifocality of LGD, and exposure to chromoendoscopy during follow-up. These variables were used in a final multivariate Cox proportional hazards model to obtain hazard ratios for each relative to baseline risk. From this we obtained an estimated linear predictor coefficient that we then apply in our prognostic tool UC-CaRE which computes the predicted future risk of cancer occurrence over a 10 year period. Results: The UC-CaRE tool is easily accessible online using the following web-link: http://www.uc-care.uk/ and provides the user with the patient's predicted cumulative HGD and/or CRC risk both quantitatively, in terms of percentage chance at yearly follow-up times up until 10 years, and visually with the aid of a Paling chart of 100 patients with the same risk, coloured according to how many of the total may develop a neoplasm in 1, 5, and 10 years. The resultant risk report can be downloaded onto computer or smartphone device for the user's reference. Conclusions: We have formulated a novel online tool that could be used in the clinic or at the bedside to aid personalised CRC risk stratification, patient education and challenging management decision-making for UC patients diagnosed with LGD. We are now in the process of externally validating our tool using independent patient cohorts from two other UK tertiary referral centres. References: 1. Choi CH, Ignjatovic-Wilson A, Askari A, et al . Low-grade dysplasia in ulcerative colitis: Risk factors for developing high-grade dysplasia or colorectal cancer. Am J Gastroenterol 2015;10:1461–1471.